Chromatin arranges in chains of mesoscale domains with nanoscale functional topography independent of cohesin - Miron, E; Oldenkamp, R; Brown, JM; Pinto, DMS; Xu, CS; Faria, AR; Shaban, HA; Rhodes, JDP; Innocent, C; de Ornellas, S; Hess, HF; Buckle, V; et al. (American Association for the Advancement of Science, 2020)
Three-dimensional (3D) chromatin organization plays a key role in regulating mammalian genome function; however, many of its physical features at the single-cell level remain underexplored. Here, we use live- and fixed-cell 3D super-resolution and scanning electron microscopy to analyze structural and functional nuclear organization in somatic cells. We identify chains of interlinked ~200- to 300-nm-wide chromatin domains (CDs) composed of aggregated nucleosomes that can overlap with individual topologically associating domains and are distinct from a surrounding RNA-populated interchromatin compartment. High-content mapping uncovers confinement of cohesin and active histone modifications to surfaces and enrichment of repressive modifications toward the core of CDs in both hetero- and euchromatic regions. This nanoscale functional topography is temporarily relaxed in postreplicative chromatin but remarkably persists after ablation of cohesin. Our findings establish CDs as physical and functional modules of mesoscale genome organization.